STRATEGI GURU AL-QUR’AN HADITS DALAM MENINGKATKAN KUALITAS BACAAN AL-QUR’AN SISWA KELAS X MAS PLUS AL-ULUM MEDAN - Nasution, Syukri Kurniawan; Junaidi, Junaidi (Islamijah: Journal of Islamic Social Sciences, 2023)
The Al-Qur'an is a guide or guide for Muslims, so as Muslims it is recommended that you be able to read the Al-Qur'an properly and correctly according to the rules of tajwid and tahsin. The quality of reading the Qur'an is very important in assessing the ability to read the Qur'an properly and correctly. This research was carried out to: (1) determine the quality of the Al-Qur'an reading of X MAS Plus Al-Ulum Medan students, (2) the strategies of Al-Qur'an Hadith teachers in improving the quality of Al-Qur'an reading of X MAS Plus Al students -Ulum Medan, (3) supporting and inhibiting factors for Al-Qur'an Hadith teachers in improving the quality of Al-Qur'an reading for class X MAS Plus Al-Ulum Medan students. This research is a qualitative research. This research is field research and this research is classified into descriptive qualitative research. The research data was collected by observing, interviewing and documenting.